The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1523/jneurosci.3353-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

L-Tyrosine Contributes to (+)-3,4-Methylenedioxymethamphetamine-Induced Serotonin Depletions

Abstract: The specific mechanisms underlying (+)-3,4-methylenedioxymethamphetamine (MDMA)-induced damage to 5-HT terminals are unknown. Despite the hypothesized role for dopamine (DA) and DA-derived free radicals in mediating this damage, it remains unclear why MDMA produces long-term depletions of 5-HT in brain regions that are sparsely innervated by DA neurons. We hypothesized that the precursor to DA biosynthesis, tyrosine, mediates MDMA-induced 5-HT depletions. Extracellular tyrosine concentrations increased fivefol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 57 publications
4
35
0
Order By: Relevance
“…The lack of serotonergic neurotoxicity by METH and MDMA in this study may be due to lack of a sufficient number of dopaminergic neurons or little interaction between dopaminergic and serotonergic neurons in the mesencephalic slice culture. Consistently, it was reported that systemic injection of MDMA produced serotonergic neurotoxicity, while local injection of MDMA into the brain had no effect (33). On the other hand, sustained exposure to 5-MeO-DiPT dramatically decreased the intracellular 5-HT tissue contents and […”
Section: Introductionsupporting
confidence: 57%
“…The lack of serotonergic neurotoxicity by METH and MDMA in this study may be due to lack of a sufficient number of dopaminergic neurons or little interaction between dopaminergic and serotonergic neurons in the mesencephalic slice culture. Consistently, it was reported that systemic injection of MDMA produced serotonergic neurotoxicity, while local injection of MDMA into the brain had no effect (33). On the other hand, sustained exposure to 5-MeO-DiPT dramatically decreased the intracellular 5-HT tissue contents and […”
Section: Introductionsupporting
confidence: 57%
“…The L-DOPA formed through this pathway can then be converted to DA via aromatic amino acid decarboxylase in 5-HT neurons. This aberrant formation of DA within presumably 5-HT neurons may not only contribute to MDMA-induced DA release in the DA-sparse hippocampus but also may contribute to DA-derived oxidative damage to 5-HT terminals (Breier et al, 2006).…”
Section: Prefrontal Cortex-mentioning
confidence: 99%
“…An additional mechanism by which high doses of MDMA may increase extracellular concentrations of DA in the hippocampus is through an increase in brain tyrosine (Breier et al, 2006). However, the increase in DA produced by elevations in tyrosine does not appear to be through activation of tyrosine hydroxylase but rather through the non-enzymatic hydroxylation of tyrosine to DOPA caused by the increase in hydroxyl radicals following administration of MDMA (Shankaran et al, 1999a, b;Colado et al, 1997).…”
Section: Prefrontal Cortex-mentioning
confidence: 99%
“…In light of the central role of monoamine transporters in mediating the pharmacological actions of MDMA, it was decided to investigate the effects of the MDMA analogues on NET and SERT transport in vitro, using two separate mammalian cell lines. Although the significance of DAT in mediating both the physiological and potentially toxicological effects of MDMA should not be underestimated (Colado et al, 2004;Breier et al, 2006;Rothman and Baumann, 2006), MDMA has typically demonstrated a greater inhibitory potency at NET and SERT compared to DAT in vitro (Rothman and Baumann, 2003;Pifl et al, 2005;Verrico et al, 2005). Consequently, it was decided to perform this investigation using NET and SERT.…”
mentioning
confidence: 99%